A Study on The HealthStatusof Tribal people in Kandhamal district, Odisha - Bhoi, Anupama; Bhoi, Anupama; Behera, Manoj Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Despite remarkable world-wide progress in the field of diagnostics and preventive health care, still there are many group of people living in isolation in the lap of natural surroundings far away from civilization with their traditional values, customs, beliefs and myths intact. Although the census 2011 enumerate the total population of scheduled Tribe at 10, 42, 18,034 persons constitute 8.6 percent of the population of the country the tribal communities in India. The number of individual groups notified as scheduled Tribe is 705. While it is not possible to provide detailed description of the demographic futures and socio economic status of each of these tribal groups. The state of Orissa occupies a unique position in the Tribal map of India having 62 scheduled tribes including 13 primitive tribes. Odisha is the one of the most fascinating ethnographic state in India. The district Kandhamal ranked as one of the backward districts amongst 69 identified most backwards district of independent India. Inhabitant here mainly depend on gathering forest product and shifting cultivation throughout the year which is the prime occupation and profession as well.Beyond their life style, occupation and profession health care has been a major problem and it has been drastically influencing all other socio economic life and livelihood of Kandhas in Kandhamal district. It is basically observed that most of the Tribal people are highly prone to disease caused by mosquito bite, impure water, sanitation, poverty, superstition, illiteracy and so on. The main objective of this research is to find the causes and current health problem of the Kandhas inhabitant of Kandhamal district. The main objectives of the research are to identify the health problem of tribal people in Kandhamal, to assess the health awareness and consciousness of the people on health and hygiene, suggest remedial measure for better health and hygiene.